KAJIAN BEBERAPA VARIETAS UNGGUL PADI GOGO DI LAHAN SAWAH KABUPATEN MAJALENGKA, JAWA BARAT - Yati Haryati; Bebet Nurbaeti (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
Strategies through mitigation, adaptation and anticipation of climate change, such as the use of adaptive crop varieties is required the impact of diversity and climate change such as drought on rice crops in the dry season. The research aimed to know agronomic and economic performances of some superior upland rice varieties as well as to obtain improved rice varieties of which are adaptive and economically viable in paddy fields in of Majalengka Regency. The study was conducted at farmer’s land of Gangsa I Farmer Group, Jatitengah Village, Jatitujuh Subdistrict, Majalengka Regency in April - July 2016 using Randomized Block Design (RBD) The treatments consisted of 5 varieties, i.e. Inpago 5, 8, 9, Situ Patenggang and Situ Bagendit and with 5 replications. Rice cultural practice that utilized an Integrated Crop Management (ICM) Approach. The observed variables were plant height, number of productive tillers, lenght length, number of grains of contents per panicle, number of unhulled grain per panicle, 1000 grain weight and productivity. Data were analyzed using Duncan Test followed by multiple distance test (DMRT) using SAS version 9.0 for windows. The result of the study showed that there were variation of variables observed including their economic farming analysis among the rice varieties.  Rice of Situ Bagendit variety gave relatively better agronomic and economic performances than those of other rice varieties, its average yield was 8.59 t ha-1 with R/C value of 2.26, therefore, it can be as an alternate rotation rice varieties in the same agro-ecosystem suited to the growing season in Majalengka Regency. ABSTRAKStrategi yang tepat melalui mitigasi, adaptasi dan antisipasi perubahan iklim, seperti penggunaan varietas tanaman yang adaptif diperlukan untuk mengantisipasi dampak keragaman dan perubahan iklim seperti kekeringan pada tanaman padi di musim kemarau. Tujuan penelitian untuk mengetahui keragaan agronomi dan ekonomi beberapa varietas unggul padi gogo serta mendapatkan varietas unggul padi gogo yang adaptif dan layak secara ekonomis di lahan sawah di Kabupaten Majalengka. Kajian dilaksanakan di lahan petani Kelompok Tani Gangsa I, Desa Jatitengah, Kecamatan Jatitujuh, Kabupaten Majalengka pada Bulan April - Juli 2016 dengan menggunakan Rancangan Acak Kelompok (RAK). Perlakuannya terdiri dari 5 varietas, yaitu Inpago 5, 8, 9, Situ Patenggang dan Situ Bagendit dengan 5 ulangan. Teknologi budidaya yang diterapkan yaitu Pendekatan Model Pengelolaan Tanaman Terpadu (PTT).  Peubah yang diamati adalah Tinggi Tanaman, Jumlah Anakan Produktif, Panjang Malai, Jumlah Gabah Isi Per Malai, Jumlah Gabah Hampa Per Malai, Bobot 1000 Butir dan Produktivitas padi. Data dianalisis menggunakan Uji Duncan dilanjutkan dengan uji jarak berganda (DMRT) dengan menggunakan SAS versi 9.0 for windows. Hasil kajian menunjukkan bahwa ada keragaman dari peubah yang diamati termasuk hasil analisis usahataninya antar varietas padi gogo.  Varietas Situ Bagendit memberikan keragaan agronomi dan analisis usahatani yang relatif lebih baik dari varietas padi gogo lainnya, hasil rata-rata gabah kering panennya 8,59 t ha-1 dengan nilai R/C 2,26, sehingga dapat dijadikan alternatif pergiliran varietas pada agroekosistem yang sama disesuaikan dengan musim tanam di wilayah Kabupaten Majalengka.